2017
DOI: 10.1007/s12630-017-0865-5
|View full text |Cite
|
Sign up to set email alerts
|

Malignant hyperthermia susceptibility in patients with exertional rhabdomyolysis: a retrospective cohort study and updated systematic review

Abstract: Findings from the Canadian patient cohort and the systematic review all signal a potential association between MH susceptibility and ER. The presence of MH-causative mutations and putative deleterious RYR1 variants in ER patients without a history of adverse anesthetic reactions suggests their possible increased risk for MH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
0
26
1
2
Order By: Relevance
“…Pediatric and male predominance of heat sensitivity in humans and mice with MHS-associated mutations. Human RYR1 mutations that underlie MHS are also frequently associated with heat and/or exercise-induced rhabdomyolysis, exercise intolerance, heat-induced muscle cramps, and death 19,[38][39][40] . We conducted a retrospective cohort study and systematic review on RYR1 variants, age, gender, clinical symptoms and survival outcomes observed in heat-sensitive individuals with RYR1 variants associated with MHS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric and male predominance of heat sensitivity in humans and mice with MHS-associated mutations. Human RYR1 mutations that underlie MHS are also frequently associated with heat and/or exercise-induced rhabdomyolysis, exercise intolerance, heat-induced muscle cramps, and death 19,[38][39][40] . We conducted a retrospective cohort study and systematic review on RYR1 variants, age, gender, clinical symptoms and survival outcomes observed in heat-sensitive individuals with RYR1 variants associated with MHS.…”
Section: Resultsmentioning
confidence: 99%
“…The same information from family members, who carried the same genetic variant was collected. Clinical case reports published between 1980 and 2019 were systematically reviewed as previously described 38 to identify additional eligible patients, using the preferred reporting items for systematic reviews and meta-analysis guidelines. The statement and checklists for the systematic reviews and meta-analysis are provided as Supplementary Notes 1-3.…”
Section: Methodsmentioning
confidence: 99%
“…Functional studies and high-resolution modeling of RyR1 showed that the MH-associated mutations adjacent to p.Gly159Arg render the RyR1 channels more sensitive to agonists and lessen thermal stability of the RyR1, thereby conferring a temperaturesensitive phenotype to mutation carriers. 21,22 As RYR1-related awake MH episodes share genetic changes with anesthetic-induced MH, 23 dantrolene may be of value for their treatment. Dantrolene stabilizes the closed state of the RyR1 channel, thereby inhibiting excessive Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that we have left out variants that are actually pathogenic using these strict criteria as many had REVEL scores >0.50 and/or were very rare but, considering all factors, were predicted as being Class 2 variants (e.g., D943N in the RYR1 gene with a REVEL score of 0.725 and MAF 0.0009) ( Table 1). The statin-tolerant controls carrying probably pathogenic variants should still be monitored for muscle symptoms during statin therapy over time since, by definition, 'awake state' phenotypes caused by pathogenic variants in MH-causing genes must be initiated by environmental triggers including but not limited to anesthesia, exertion, heat stroke and statin therapy [28,70]. The two positive controls may be at risk for MHS, but may also have other genetic variants or lifestyle habits that make them less susceptible to statin side effects or the dose of statin taken did not exceed a threshold for triggering muscle symptoms in these cases.…”
Section: Discussionmentioning
confidence: 99%